Effect on Plasma Parameters in a Dielectric Barrier Discharge Reactor with Volatile Organic Compounds - Mohanty, S.; Das, S. P.; Sahoo, G.; Paikaray, R.; Das, P. S.; Samantaray, S.; Patil, D. S. (Kathmandu University Journal of Science, Engineering and Technology, 2014)
A Dielectric barrier discharge (DBD) device is set up in Ravenshaw University, Cuttack, India to study the plasma assisted destruction of volatile organic pollutants like nitro - benzene and chloro-benzene etc. Plasma parameters like electron density and temperature for argon plasma is measured using spectroscopic technique. The electron temperature of plasma is found to be ~ 1.81 eV for applied voltage 7 kV, MFC at the rate of 1 lit/min and the plasma current is ~ 0.31 mA. When the applied voltage is increased electron temperature as well as electron density increases so also the plasma current showing enhancement of ionization. Volatile organic compound like nitro-benzene on treatment with argon plasma environment inside DBD reactor increases electron temperature in the system and the electron density also increased twice. On the other hand when chlorobenzene is treated with plasma the electron temperature in the system decreases appreciably so also electron density. This indicates the dissociation of chlorine from benzene to neutralize free electrons of argon plasma acting as electron scavenger.